GESTUR DALAM PEMBELAJARAN MATEMATIKA MATERI IRISAN KERUCUT DAN KOORDINAT POLAR - Yunis Sulistyorini (Program Studi Pendidikan Matematika, 2019)
Gestures played a role in the learning of mathematics, especially in the Sliced Cone and Polar Coordinates material. Educators gestures associated with conceptual planning of the explanations and is the embodiment of knowledge and understanding of educators associated with the material being studied. The educators’ gestures were pointing gestures, representations and writing. Gestures appeared at the planning stage, especially the activities of peer teaching and learning implementation. Both of two steps related to the implementation of lesson study in math learning. Gestures accompanied explanations educators help to clarify, explain, and emphasize mathematical concepts in the material being studied.